004. Dynamics of QT interval from rest to peak exercise among chronic obstructive pulmonary disease (COPD) patients - Boutou, Afroditi (J Thorac Dis, 2015)
BACKGROUND: Cardiovascular involvement is frequent in chronic obstructive pulmonary disease (COPD), with autonomic dysfunction a recognized feature. However, the dynamics of QT interval, a known marker of autonomic dysfunction, from rest to peak exercise in COPD patients has not yet been investigated. The aim of this study was to examine the changes in QT, heart-rate corrected QT (QTc), PR, QRS and RR intervals from rest to peak exercise in a population of stable COPD outpatients and of healthy controls. METHODS: Prospectively collected data on COPD patients and healthy controls who underwent spirometry and maximum cardiopulmonary exercise testing with a continuous 12- lead ECG recording, were retrospectively analyzed. Distribution of variables was assessed with Shapiro-Wilk test and group comparisons were conducted utilizing the paired samples t-test or Wilcoxon rank test, as appropriate. Level of P<0.05 was considered significant. RESULTS: The study population consisted of 143 patients (63.6% male; 62.8±7.4 years old; FEV(1)%=32.3±14) and 18 age and gender-matched controls. Among controls, QT, PR and RR intervals were shortened while QTc was prolonged from rest to peak exercise. Among COPD patients, QTc interval did not change. QT, PR and RR intervals were shortened, but absolute changes were smaller, compared to the ones of controls. Patients under drugs which are known to prolong QT had similar QT, compared to the ones under no such drugs. CONCLUSIONS: COPD patients demonstrate a different exercise response; QTc interval is not prolonged, while the shortening of QT is about 30% of what expected when compared to healthy controls.